Fish processing : sustainability and new opportunities - Hall, George M. (Wiley-Blackwell, 2011)
The seafood processing industry offers a good example of the difficulties in applying sustainability principles to a complex set of relationships, involving not just the technologies which could militate against environmental damage but also the economics and human societal imperatives behind them